Análise molecular dos genes PROP1 e HESX1 em pacientes com displasia septo-ótica e/ou deficiência hormonal hipofisária - Cruz, Juliana B. [UNESP] (2010)
Objective: The present study aimed at evaluating the PROP1 and HESX1 genes in a group of patients with septo-optic dysplasia (SOD) and pituitary hormone deficiency (combined - CPHD; isolated GH deficiency - GHD). Eleven patients with a clinical and biochemical presentation consistent with CPHD, GHD or SOD were evaluated. Subjects and methods: In all patients, the HESX1 gene was analyzed by direct sequence analysis and in cases of CPHD the PROP1 gene was also sequenced. Results: A polymorphism (1772 A > G; N125S) was identified in a patient with SOD. We found three patients carrying the allelic variants 27 T > C; A9A and 59 A > G; N20S in exon 1 of the PROP1 gene. Mutations in the PROP1 and HESX1 genes were not identified in these patients with sporadic GHD, CPHD and SOD. Conclusion: Genetic alterations in one or several other genes, or non-genetic mechanisms, must be implicated in the pathogenic process. Copyright© ABE&M todos os direitos reservados.